Pendekatan Bermain untuk Menurunkan Perilaku Menghindar pada Anak yang Mengalami Trauma Pengobatan - Sumiati Sumiati; Ambar Sulianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
Trauma is emotional response that involve intense fear, helplessness, or horror. Trauma raises three reactions i.e. disrupt memory, avoidance behavior and emergence of physical disorders. Children love games. This study aimed to test the effect of the playing approach against avoidance behaviors in a child with treatment trauma due to chronic disease. This study used a quasi experimental by Single Subject Randomized Time Series Design. The research subject was a seven years old child who suffering chronic Lyme disease with a fist size swelling in her face who showed avoidance behaviour trauma. Lego, drawing, folding, and story telling have been choosen as playing approach. The avoidance behaviour were observed consists of treatment avoidance and laboratory avoidance. The data were analyzed using descriptive statistical analysis in the form of graphs. The results shown that playing method had lowering effect in both avoidance behaviors.